Exogenous enzymes in sheep diet: nutritional and physiological parameters - Neiva, Maíra Costa; Schultz, Erica Beatriz; Sousa, Luciana Melo [UNESP]; Oliveira, Karla Alves [UNESP]; Sousa, Luciano Fernandes; Macedo Junior, Gilberto de Lima (Universidade Estadual de Maringa, 2022)
The objective of this study was to evaluate the effect of adding exogenous enzymes to the diet on nutrient intake and digestibility, nitrogen balance, ingestive behavior and rumen movement of ewe lambs. Five ewe lambs, Dorper x Santa Inês crossbred, with an average age of 7 ± 1 months, average weight of 36.40 ± 2.36 kg were assigned in a 5x5 Latin square design. The treatments consisted of adding exogenous enzymes to the concentrate: Allzyme, Fibrozyme®, Amaize®, Mix and Control. Analyses of variance were applied and means were compared by the SNK test, and non-parametric Kruskal Wallis test at 5% significance. The dry matter intake in relation to body weight, crude protein intake and nitrogen intake were higher with the use of amylolytic enzyme compared to the other treatments (p <0.05). Nitrogen balance was higher with the use of amylolytic enzymes and the Allzyme® enzyme complex (p <0.05). A longer time spent in total chewing was observed with the inclusion of fibrolytic and amylolytic enzymes without changes in rumen movement. The use of exogenous enzymes promotes better use of nutrients, with high digestibility of dry matter, neutral detergent fiber and crude protein.
Keywords: fiber; Ovis aries; protein; starch